Chapter Una terra senza nome. Sviluppo economico e identità collettive nella bassa pianura milanese (tardo medioevo-prima età moderna) - DEL TREDICI, FEDERICO (Reti Medievali E-Book, 2021)
In the Historia de situ Ambrosianae urbis, written in the early fourteenth century, the notary Giovanni of Cermenate offered an unprecedented tripartite image of the Milanese contado: Seprio, north-west; Martesana, north-east; and a third indefinite "part" which can be identified with the plain south of the city, not exactly defined by Giovanni of Cermenate. The paper investigates such an absence, by linking it to the general weakness of collective identities provoked by the extraordinary economic development of the low Milanese plain.